A data-driven investigation on park visitation and income mixing of visitors in New York City. (March 2023) - Wei, Hanxue; Huang, Xiao; Wang, Sicheng; Lu, Junyu; Li, Zhenlong; Zhu, Liao
It is crucial to understand the current pattern of urban park visitation to achieve environmental justice. Current discussions of environmental equity of parks mainly focus on the inequality provision measured by park accessibility, park area, park quality, and park congestion, ignoring the inequity of social benefits through interactions among mixed-income groups. Based on fine-grained mobile phone location data at the census block group level in 2018 and 2019, we explored visitation patterns and the mixed-income levels of visitors in urban parks in New York City. The visitors were divided into five income groups, with the "income entropy" used as a measure of the mixed level of the visitors in terms of income groups. We answered an important question: what factors affect the visitation intensity and the mixed level of income groups in urban park visitors? Our results revealed that the time of year and season, the parks' characteristics, the built environment, and the socioeconomic characteristics of the park's surrounding neighborhoods have strong associations with park use patterns. We also offered implications for urban planning and urban design to promote park visitation and income-diverse park use and improve social inclusion and environmental equity.